Learning OpenStack networking : build a solid foundation in virtual networking technologies for OpenStack-based clouds - Denton, James (Packt Publishing, 2018)
This third edition of Learning OpenStack Networking is for OpenStack-based cloud operators and administrators who are new to Neutron networking and want to build their very own OpenStack cloud. Prior networking experience of working with physical servers and network infrastructures is recommended to follow the concepts demonstrated in this book.